The CBM Physics Book Compressed Baryonic Matter in Laboratory Experiments - Friman, Bengt; Höhne, Claudia; Knoll, Jörn; Leupold, Stefan; Randrup, Jorgen; Rapp, Ralf; Senger, Peter (Lecture Notes in Physics,, 2011)
This exhaustive survey is the result of a four year effort by many leading researchers in the field to produce both a readable introduction and a yardstick for the many upcoming experiments using heavy ion collisions to examine the properties of nuclear matter. The books falls naturally into five large parts, first examining the bulk properties of strongly interacting matter, including its equation of state and phase structure. Part II discusses elementary hadronic excitations of nuclear matter, Part III addresses the concepts and models regarding the space-time dynamics of nuclear collision experiments, Part IV collects the observables from past and current high-energy heavy-ion facilities in the context of the theoretical predictions specific to compressed baryonic matter. Part V finally gives a brief description of the experimental concepts. The book explicitly addresses everyone working or planning to enter the field of high-energy nuclear physics.